The Effect Of Capital Structure And Profitability On Tax Avoidance In Manufacturing Companies Listed On The Idx 2013-2017 - et. al., Radhi Abdul Halim Rachmat, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Tax avoidance is currently the main concern of almost all countries. This study entitled The Effect of Capital Structure and Profitability on Tax Avoidance in Manufacturing Companies Listed on the Stock Exchange in 2013-2017. The purpose of this study is to determine the effect partially and simultaneously Capital Structure and Profitability on Tax Avoidance in Manufacturing Companies. The research method used is explanatory method with the sampling technique using purposive sampling with sampling technique is purposive sampling. From the sampling results obtained a sample of 49 companies. The data source used was obtained through the site ww.idx.co.id. The analysis tools used are panel data regression, determination test and hypothesis test (t-test) using Eviews 9. The results showed that the capital structure and profitability partially and simultaneously affect tax avoidance.